CONSTRUCTION OF COMPUTATIONAL 3D STRUCTURES OF PROTEIN DRUG TARGETS OF MYCOBACTERIUM TUBERCULOSIS - RAO, SUDHIR; SAYEEDA, MISBAH; PRAKASH, TEJASHREE; AP, PADMASHREE; IMRAN, SABIA; RAVI, LOKESH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This study aims in constructing a three-dimensional modeled protein structure of potential drug targets in Mycobacterium tuberculosis bacteria. Methods: The protein models were constructed using SWISS-Model online tool. The constructed protein models were submitted in online database called Protein Model Database (PMDB) for public access to the structures. Results: A total of 100 protein sequences of M. tuberculosis were retrieved from UniProt database and were subjected for sequence similarity search and homology model construction. The constructed models were subjected for Ramachandran plot analysis to validate the quality of the structures. A total of 69 structures were considered to be of significant quality and were submitted to the online database PMDB. Conclusion: These predicted structures would help greatly in identification and drug design to various strains of M. tuberculosis that are sensitive and resistant to different antibiotics. This would greatly help in drug development and personalized drug treatment against different strains of the pathogen. This database would significantly support the structure-based computational drug design applications toward personalized medicine in regard to differences in the various strains of the pathogen.